Comparison of comorbidities of migraine and tension headache in a pediatric headache clinic. (October 2017) - Eidlitz-Markus, Tal; Zolden, Shirit; Haimi-Cohen, Yishai; Zeharia, Avraham
Objective: To compare comorbidities between migraine and tension headache in patients treated in a tertiary pediatric headache clinic. Methods: Files of patients with migraine or tension headache attending a pediatric headache clinic were retrospectively reviewed for the presence of organic comorbidities. Additionally, patients were screened with the self-report Strengths and Difficulties Questionnaire to identify nonorganic comorbidities. If necessary, patients were referred to a pediatric psychiatrist, psychologist or social worker for further evaluation. Results: The study cohort comprised 401 patients: 200 with migraine and 201 with tension headache. The main organic comorbidities were atopic disease, asthma, and first-reported iron-deficiency anemia; all occurred with statistical significance more often with migraine than with tension headache (Familial Mediterranean fever was six times more frequent in the migraine group than in the tension headache group, but the difference was not statistically significant. Nonorganic comorbidities (psychiatric, social stressors) were associated significantly more often with tension headache than with migraine (48.3% versus 33%; p  = 0.03). Conclusions: Children and adolescents with migraine or tension headache treated in a dedicated clinic have high rates of organic and nonorganic comorbidities. In this setting, patients with migraine have significantly more organic comorbidities, and patients with tension headache, significantly more nonorganic comorbidities.